PENGARUH DEBT TO ASSET RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Mega Selpia; Nisfu Fhitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study was conducted to determine the effect of Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on Return on Assets (ROA) in Property and Real Estate Companies Listed on the Indonesia Stock Exchange. The population in this study were Property and Real Estate Companies listed on the Indonesia Stock Exchange. The sample was taken using purposive sampling, resulting in 36 observations. And using multiple linear regression methods, classical assumption tests, simultaneous tests (F tests), and partial tests (t tests). The results of this study indicate that the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) simultaneously influence Return on Assets (ROA) with a calculated F value > F table (31.147 > 2.90). The partial test results for the DAR and DER variables do not affect ROA because the DAR significance value is 0.069 > 0.05 and -t count (-1.879) < -t table (-2.03452). The DER variable has a partial significance of 0.360 > 0.05 with a calculated t value of 0.929 < t table (2.03452). The TATO variable has a partial significance of 0.000 < 0.05, with a calculated t value of 8.006 > t table of 2.03452. Partially, the TATO variable has a positive and significant effect on ROA. The Adjusted R Square value, or coefficient of determination, is 0.721. This means that 72.1% of the variation or change in Return on Assets is explained by variations in the Debt to Asset Ratio, Debt to Equity Ratio, and Total Asset Turnover, while 27.9% is influenced by other variables outside the research model.  Keywords: Debt to Asset Ratio, Debt to Equity Ratio, Total Asset Turnover, and Return on Assets   Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), dan Total Asset Turnover (TATO) terhadap Return on Assets (ROA) pada perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia. Data yang digunakan adalah data sekunder. Sampel penelitian terdiri dari 36 pengamatan yang dipilih menggunakan teknik purposive sampling. Teknik analisis yang digunakan adalah analisis regresi linier berganda dengan uji asumsi klasik, uji simultan (uji F), dan uji parsial (uji t). Hasil penelitian menunjukkan bahwa seluruh variabel independen secara simultan berpengaruh signifikan terhadap Return on Assets, dengan nilai Fhitung 31,147 > Ftabel 2,90. Secara parsial, Debt to Asset Ratio (DAR) tidak berpengaruh signifikan terhadap Return on Assets dengan nilai thitung -1,879 < ttabel -2,03452 dan nilai signifikansi 0,069 > 0,05. Debt to Equity Ratio (DER) tidak berpengaruh signifikan dengan nilai thitung 0,929 < ttabel 2,03452 dan nilai signifikansi 0,360 > 0,05. Total Asset Turnover (TATO) berpengaruh positif dan signifikan terhadap Return on Assets dengan nilai thitung 8,006 > ttabel 2,03452 dan nilai signifikansi 0,000 < 0,05. Nilai Adjusted R Square sebesar 0,721 yang berarti bahwa 72,1% variasi Return on Assets dapat dijelaskan oleh DAR, DER, dan TATO, sedangkan 27,9% dipengaruhi oleh variabel lain di luar model penelitian.  Kata Kunci: Debt to Asset Ratio, Debt to Equity Ratio, Total Asset Turnover, Return on Assets